2005
DOI: 10.1128/aem.71.4.2106-2112.2005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Biomarkers and Carbon Isotope Signatures of a Microbial ( Beggiatoa ) Mat Associated with Gas Hydrates in the Gulf of Mexico

Abstract: White and orange mats are ubiquitous on surface sediments associated with gas hydrates and cold seeps in the Gulf of Mexico. The goal of this study was to determine the predominant pathways for carbon cycling within an orange mat in Green Canyon (GC) block GC 234 in the Gulf of Mexico. Our approach incorporated laser-scanning confocal microscopy, lipid biomarkers, stable carbon isotopes, and 16S rRNA gene sequencing. Confocal microscopy showed the predominance of filamentous microorganisms (4 to 5 m in diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 72 publications
(55 reference statements)
3
73
0
2
Order By: Relevance
“…However, in the meth-anogenesis zone, abundant 16:1ω6, 16:1ω8, 18:1ω6, 16:1ω8 also are expected (Zhang et al, 2005 and references therein) [27]. Lacking of monounsaturated fatty acids in this study rules out the possibility of methanogens were a main source.…”
Section: Identification Of Sulfate-reducing Bacteria and Sulfur-oxidimentioning
confidence: 80%
See 3 more Smart Citations
“…However, in the meth-anogenesis zone, abundant 16:1ω6, 16:1ω8, 18:1ω6, 16:1ω8 also are expected (Zhang et al, 2005 and references therein) [27]. Lacking of monounsaturated fatty acids in this study rules out the possibility of methanogens were a main source.…”
Section: Identification Of Sulfate-reducing Bacteria and Sulfur-oxidimentioning
confidence: 80%
“…Third, it has been shown that i15:0, a15:0, i17:0 and a17:0 fatty acids can be synthesized by microbes [30]. Finally, bacteria have been shown to have fatty acids with carbon numbers mainly between C 12 to C 20 , containing abundant branched saturated and monounsaturated fatty acids [20,[22][23][24][25][26][27]31,32]. The fatty acids detected in this study contained branched saturated fatty acids (e.g.…”
Section: Origin Of Fatty Acidsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, as reported by Ben-Mlih et al (1992), an absence of the usual phytoplankton markers (e.g., 20:5ω3 or 22:6ω3) and the high levels of bacterial populations lead to the conclusion that all the ω7 series are of bacterial origin. Furthermore, many previous studies of the gas hydrate and cold seep settings widely considered C16:1ω7 and C18:1ω7 as the signature biomarker for SOB (McCaffrey et al, 1989;Guezennec and Fiala-Medioni, 1996;Zhang et al, 2005;Li et al, 2007). Therefore, the possible sources of 16:1ω7 and 18:1ω7 acids are considered SOB in the present study, which is a major primary producer in the seafloor hydrothermal environment (Jannasch, 1983;Hedrick et al, 1992;López-García et al, 2003).…”
Section: Saturated Fatty Acidmentioning
confidence: 99%